Causal associations of white blood cell count and sudden sensorineural hearing loss: a bidirectional and multivariable Mendelian randomization study - Zhang, Ling; Chen, Jialei; Zhong, Shixun; Luo, Jing; Tang, Ping (Frontiers in Neurology, 2024)
Background Numerous compelling observational studies have demonstrated a plausible correlation between the white blood cell count and the susceptibility to sudden sensorineural hearing loss (SSNHL). Nevertheless, the exact causal relationship between these two factors remains ambiguous. The objective of our study was to assess the causal impact of white blood cell count on sudden sensorineural hearing loss through the implementation of a bidirectional and multivariable Mendelian randomization (MR) methodology. Methods Genetic data pertaining to white blood cell count were acquired from the Blood Cell Consortium, encompassing a total of 563,946 subjects. Concurrently, summary data on sudden sensorineural hearing loss were sourced from a Genome-Wide Association Study (GWAS), involving 196,592 participants, comprising 1,491 cases and 195,101 controls. The primary method employed for MR analysis was the Inverse Variance Weighted method (IVW), while sensitivity analysis utilized the Weighted Median method, MR-Egger method, and MR-PRESSO method. Results In IVW method, genetically predicted elevated lymphocyte cell count demonstrates an effective reduction in the risk of sudden sensorineural hearing loss (odds ratio = 0.747, 95% CI = 0.565–0.987, p = 0.04). These findings remain consistent in multivariate MR analysis, even after adjusting for monocyte cell count and neutrophil cell count levels (odds ratio = 0.929, 95% CI = 0.867–0.995, p = 0.036). However, there is no discernible evidence supporting a direct causal relationship between monocyte cell count and neutrophil cell count levels and the occurrence of SSNHL. Conclusion Within the normal range, higher lymphocyte cell count levels exhibit a potential protective effect against SSNHL. Meanwhile, no direct causal relationship are identified between monocyte cell count and neutrophil cell count levels and the risk of SSNHL.